Reducing Opioid Overprescribing through Procedure-specific Prescribing Guidelines. Issue 1 (20th January 2023) - Zhang, Kevin K.; Blum, Kevin M.; Chu, Jacqueline J.; Sharma, Shuchi; Skoracki, Roman J.; Moore, Amy M.; Janis, Jeffrey E.; Barker, Jenny C.
Abstract : Background: Despite advances in opioid-sparing pain management, postdischarge opioid overprescribing in plastic surgery remains an issue. Procedure-specific prescribing protocols have been implemented successfully in other surgical specialties but not broadly in plastic surgery. This study examined the efficacy of procedure-specific prescribing guidelines for reducing postdischarge opioid overprescribing. Methods: A total of 561 plastic surgery patients were evaluated retrospectively after a prescribing guideline, which recommended postdischarge prescription amounts based on the type of operation, was introduced in July 2020. Prescription and postdischarge opioid consumption amounts before (n = 428) and after (n = 133) guideline implementation were compared. Patient satisfaction and prescription frequency of nonopioid analgesia were also compared. Results: The average number of opioid pills per prescription decreased by 25% from 19.3 (27.4 OME) to 15.0 (22.7 OME; P = 0.001) after guideline implementation, with no corresponding decrease in the average number of postdischarge opioid pills consumed [10.6 (15.1 OME) to 8.2 (12.4 OME); P = 0.147]. Neither patient satisfaction with pain management (9.6‐9.6; P > 0.99) nor communication (9.6‐9.5; P > 0.99) changed. The rate of opioid-only prescription regimens decreased from 17.9% to 7.6% ( P = 0.01), and more patients were prescribed at least two nonopioid analgesics (27.5% to 42.9%; P = 0.003). The rate of scheduled acetaminophen prescription, in particular, increased (54.7% to 71.4%; P = 0.002). Conclusions: A procedure-specific prescribing model is a straight-forward intervention to promote safer opioid-prescribing practices in plastic surgery. Its usage in clinical practice may lead to more appropriate opioid prescribing.